ANALISIS KUALITAS SOAL SISWA KELAS V SEKOLAH DASAR BERDASARKAN KEMAMPUAN NUMERASI SOAL ASESEMEN KOMPETENSI MINIMUM (AKM) - Agnes Theresia; Andri Anugrahana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research was conducted to analyze the quality of each question item using numeracy skills from the minimum competency assessment questions (AKM) for fifth grade elementary school students. The aim of this research is to prove that the minimum competency assessment questions (AKM) are quality, as well as to analyze the influence of the minimum competency assessment questions (AKM) on improving the numeracy skills of fifth grade elementary school students. The method in this research is descriptive qualitative. This research used 4 validators and 15 fifth grade elementary school students as test subjects for minimum competency assessment numeracy (AKM) questions. The object of this research is a question sheet with 30 questions. Meanwhile, in the questionnaire, the researcher only took 5 students to fill in several statements on the questionnaire. Data were analyzed using SPSS to determine the value of validity, reliability, distinguishing power and level of difficulty. And using data analysis techniques in the form of triangulation by taking data from 3 students who got high, medium and low scores. Based on the validity test analysis, there are 30 valid questions, with a reliability of 0.879 (reliable), then the discriminating power analysis shows that there are 9 questions in the